Geoconservação de patrimônio espeleológico na Amazônia: proposta de planejamento ambiental para a província espeleológica Altamira-Itaituba (PA) - Freire, Luciana Martins (2017)
The Amazon region has significant diversity in geomorphological features resulting from the systemic interaction of elements of nature, among which are the speleological patrimony and its geodiversity. Speleology is an area of knowledge of multiple meanings (scientific, sport, tourism and sociocultural), which is dedicated to studying the nature, genesis and processes of formation of the natural underground caverns (caves, shelters, etc.) and their related features, including their biological aspects. In this context, the research is developed in the Altamira-Itaituba Speleological Province, in the state of Pará, located in the contact of the geological domains of located in the contact strip of that following geologic domains: Amazonas Sedimentary Basin and of basement of Xingu Complex. The main objective is to present a diagnosis of the natural and cultural landscapes of this province, having as final instrument the proposal of environmental planning and geoconservation of the landscape. The Geoecology of Landscapes is the methodological basis for the construction of the proposal of environmental planning, in which it made possible a greater articulation between the different aspects of formation and operation of the landscape. The lack of conservation units in the speleological province is a concern, since these environments are configured by relief forms developed in non-carbonate karst rocks. A contribution is made to speleological research and karstic geomorphology, as well as to broaden and deepen studies aimed at the conservation of geological heritage and the geodiversity of the Amazon. Based on the integrated environmental diagnosis of the Altamira-Itaituba Speleological Province, the Limoeiro Cave and its surroundings were selected as an example of a proposal for environmental planning, from which the values of local geodiversity and geotourism potential were recognized, with a projection of visitation scenarios. Finally, a reading of environmental protection and management actions was presented along with a proposal for the Speleological Environmental Zoning applied to Limoeiro Cave. An important contribution has been made here to speleological studies in the Amazon and the appreciation of its geodiversity in the context of integrated environmental studies.